Framing Wikileaks In The Networked Fourth Estate - Maggs, Catherine Ann (AoIR Selected Papers of Internet Research, 2017)
WikiLeaks’ rise to prominence in 2010, with its release of classified U.S. government and military documents, polarised opinion worldwide; some viewed it as a cyber-terrorist group, others saw it as journalism’s saviour. This paper situates WikiLeaks within the framework of Yochai Benkler’s networked public sphere. In the age of the Internet and networked communications, the role of information gathering, investigation and analysis regarding the powerful has extended beyond the boundaries of traditional news organisations and professional journalists in what Benkler theorises as the networked fourth estate. Benkler contends the emergent forms of the networked fourth estate are increasingly vulnerable to attacks from institutional media fearful of the decentralisation they represent. Placing WikiLeaks within the context of the networked fourth estate, the paper analyses WikiLeaks’ depiction in two major political journals of record by identifying the construction and use of media frames in the editorial pages of _The New York Times_ and _The Washington Post_. As a technologically novel, politically reformist and internationally networked media entity, WikiLeaks can be considered as a form of alternative networked media that challenges hegemonic media and political power. The paper found the elite mainstream media news framing of WikiLeaks as transgressive and irresponsible, delegitimised the organisation’s value to public sphere discourse and reasserted the mainstream media’s central importance in the democratic public sphere. Dismissing the informational value of the disclosures denied WikiLeaks’ capacity to exercise any political counterpower that might have meaningful consequences for policy or the mainstream networked public sphere.